'Does Farming Pay in Victoria?' Profit Potential of the Farming Industry in Mid‐Nineteenth‐Century Victoria. (March 2014) - Ostapenko, Dmytro
<x xml:space="preserve">Abstract</x> The conventional view of the fortunes of European newcomers who cropped land in mid‐nineteenth‐century Victoria is confined to a description of their difficulties. This article critically assesses the scope for profit‐making in the local farming sector in the late 1830s to early 1870s. The microeconomic environment in which early colonial farmers operated is reconstructed in this article with the use of modern Michael Porter's five forces of competition model. The article shows the high profit potential of crop farming – even when on a small scale – throughout the period, with the exception of the last few years when intensified competition among farmers affected their profits.